GHARAR DALAM AKUNTANSI AKRUAL - Oktaviana, Ulfi Kartika (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2010)
Some authors  agreed that accrual basis concept is in line with the objectives of Islamic accounting.  The ones who’s  agreed  applying acrrual basis of accounting   believes that the primary objective of Islamic Accounting information is to facilitate the users in computing his or her zakah obligation. The ones who’s not agreed applying accrual basis believes that recognizing noncash and circumstances as they occur is contain gharar.  They also believes in computing zakah obligation cannot apply accrual accounting because zakah must compute base on wealth which has been receive its benefit. Definition of accrual accounting also allow earning management to occur. Debate of the cash basis and the accrual basis has been long discussion, for financial statement of Islamic bank and financial institution need modified accrual and cash basis in order to fulfills Islamic Shari’a. Key word: Gharar, Akuntansi Akrual, Akuntansi Kas, Laporan     Keuangan Entitas Syariah.